2022
DOI: 10.1155/2022/7106054
|View full text |Cite|
|
Sign up to set email alerts
|

Public Opinion Guidance and Communication Mechanism Innovation of Public Health Events Based on the Multitask Learning Network in the Internet Era

Abstract: In order to improve the public opinion guidance ability for public health events in the Internet era, and improve the the problems of the traditional public opinion guidance mechanism, we analyze the public opinion guidance and communication mechanism based on the Internet era, and analyze the guidance software and software system, and related technical requirements? subsequently, the efficiency analysis of the public opinion guidance and communication mechanism of the multitask learning network was conducted;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The novel coronavirus, first identified in late 2019, is a major public health emergency, and by the end of November 2022, the World Health Organization reported that the total number of new coronavirus pneumonia (COVID-19) cases had exceeded 625 million, with ~15 million direct and indirect deaths due to new coronaviruses ( 5 ), which are still spreading globally. In addition to COVID-19, the world has seen several other major public health emergencies in the last decade, including severe acute respiratory syndrome (SARS) in 2003, H1N1 influenza in 2009, Middle East respiratory syndrome (MERS) in 2012, and West Africa Ebola in 2014, all of which had a major impact on human society ( 6 ). These diseases seriously endangered the collective survival and harmonious coexistence of the human community of destiny and caused incalculable damage to the global economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel coronavirus, first identified in late 2019, is a major public health emergency, and by the end of November 2022, the World Health Organization reported that the total number of new coronavirus pneumonia (COVID-19) cases had exceeded 625 million, with ~15 million direct and indirect deaths due to new coronaviruses ( 5 ), which are still spreading globally. In addition to COVID-19, the world has seen several other major public health emergencies in the last decade, including severe acute respiratory syndrome (SARS) in 2003, H1N1 influenza in 2009, Middle East respiratory syndrome (MERS) in 2012, and West Africa Ebola in 2014, all of which had a major impact on human society ( 6 ). These diseases seriously endangered the collective survival and harmonious coexistence of the human community of destiny and caused incalculable damage to the global economy.…”
Section: Introductionmentioning
confidence: 99%
“…The functional, algorithmic, learning, and textual properties of digital technologies have made them a hot topic in public health management ( 14 16 ). By combing through the existing literature, we can find that emergency management of public health events driven by digital technology is mainly studied from the following perspectives: first, the use of digital technology for early warning and prediction of public health events, for example, some scholars applied big data on social media to predict health-related behaviors to prepare for and respond to public health emergencies promptly and epidemics ( 17 19 ); with the development of digital technologies, intelligent algorithms ( 8 , 20 ), machine learning ( 21 , 22 ), deep learning ( 6 , 23 ) have also been used in early warning studies of public health emergencies to extract and analyze relevant news and other information data intelligently. The application of these methods advances the intelligent emergency management of public health emergencies, thus reducing the impact of public health emergencies on society.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%